Missing: Have You Seen These Scrolls? - Justnes, Årstein (Biblical archaeology review, 2022)
The article reports on the 75th anniversary of Dead Sea Scrolls. It mentions throughout the book "Discoveries in the Judaean Desert" there are hundreds of brief notes about lost fragments, and most of these pieces are indeed very small, but they add up to quite a substantial lot. It also mentions some fragments were reported stolen from the Palestine Archaeological Museum which included a large fragment from a Samuel, Daniel, and a fragment from a non-biblical scroll named "Beatitudes."